2017
DOI: 10.1108/tqm-03-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Does the soft aspects of TQM influence job satisfaction and commitment? An empirical analysis

Abstract: Purpose Previous studies that have attempted to link TQM and employees’ satisfaction are either theoretical without empirical evidence or had limited outcome in scope as they link only few elements of TQM with employees’ job satisfaction and commitment. This study is warranted due to the paucity of insights into the impact of soft strategies on determining job satisfaction and commitment. Despite the considerable body of TQM literature that has evolved to examine the relationship between TQM and employees’ job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(95 citation statements)
references
References 59 publications
7
84
4
Order By: Relevance
“…It means that majority of the teachers in indigenous schools believe that if promotional opportunities is implemented with the right procedure, their level of commitment to stay with the schools will increase. The finding is consistent with a study by Arunachalam and Palanichamy (2017) which stated that organization should continuously improve performance appraisal policies by eliminating standards and quota-based rewards. As we know time based promotional opportunities were applied to teachers in Malaysia.…”
Section: Discussion/analysissupporting
confidence: 91%
See 2 more Smart Citations
“…It means that majority of the teachers in indigenous schools believe that if promotional opportunities is implemented with the right procedure, their level of commitment to stay with the schools will increase. The finding is consistent with a study by Arunachalam and Palanichamy (2017) which stated that organization should continuously improve performance appraisal policies by eliminating standards and quota-based rewards. As we know time based promotional opportunities were applied to teachers in Malaysia.…”
Section: Discussion/analysissupporting
confidence: 91%
“…It is suggested that the Pahang State Education Department to continuously have a good rapport with the teachers and asks the feedback regarding the job so that responsible parties might have a clear picture of what is really happening in indigenous schools in Pahang. It is supported by a study from Arunachalam and Palanichamy (2017), organizations should also concentrate on employees' development needs by providing positive feedback regularly with necessary training opportunities as a way to produce satisfied and committed employees. By having a continuous feedback from the teachers, responsible parties would also understand the needs and wants of the teachers at the schools.…”
Section: Discussion/analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both are based on the ISO 9000 standard of the year of 2005 and 2015, which contains the principles of the standards included in the system. Since ISO 9001:2008 does not regularize involvement and motivation [18], which are particularly important values for implementing open innovation, ISO 9001 focuses primarily on measuring efficiency, while ISO 9004 focuses on improving the efficiency [19], we are dealing with ISO 9004. While ISO 9001 is suitable for quality assurance of customer-specific products, ISO 9004 beyond that can be used to continuously improve performance to gradually achieve excellence [20].…”
Section: Iso 9004:2018 For Open Innovationmentioning
confidence: 99%
“…Commitment was found to be one of the TQM principles and its role was described in many works (e.g. Oakland, 1995; Arunachalam and Palanichamy, 2017; Soltani et al , 2005). Leadership plays a special role in TQM, which has been proved in many researches (e.g.…”
Section: The Current Status Of Research On the Subject As Reflected In The Tqm Literaturementioning
confidence: 99%